Design of an Appropriate Combined Sheet Metal Roll Forming and Bending Machine for Small Scale Fabrication Enterprises. - Kaggwa, William Namutale (Kabale University, 2023)
Sheet metal fabrication is an important element in the manufacturing and production in Uganda and worldwide today. Several processes such as bending and rollforming are used to change the shape or appearance, mechanical properties, and any other property of the sheet metal as required r use. To accomplish this, various machines such as bending machines, metal cutters, roller benders, and many others are used. These machines are huge, expensive, have a high-power requirement, can handle thicknesses of up to 6mm. For these reasons and more, small-scale fabrication workshops cannot buy and use them. This project intends to provide an appropriate option to these workshops instead of being charged expensively or rather send off the work to bigger workshops. To make the appropriate design, the required specifications were established, components were selected and then sized, and then a layout of the machine was generated using 3D modeling software (DS SOLIDWORKS). The design specifications were obtained from the -1: s in the available designs and the market demands. With these, components that could serve to fulfill these requirements were chosen and thereafter were sized using various formulas and -.jiematical constants as provided in this document. With these, all the components were then modeled in DS SOLIDWORKS and an assembly was also made. To conclude, implementing this project will give the target market an economized system, fitting within their very limited resources, that can be used to better their lives. The various sources of the data (references) given in this report are also provided at the end of the document.